Cinéma et urbanité à Tunis sous le protectorat français - Morgan Corriou (L’Année du Maghreb)
The development of cinema in Tunis did not seem, at first, to disrupt the geography of leisure in the city. Movie theaters were mostly located in the city center, favoring the most vibrant streets of the Tunisian capital. Exhibitors admittedly neglected the outskirts of the city. Yet movie theaters were scattered across the new town and started penetrating a medina doomed to marginalization, proving that the ancient forms of urbanization were not irreconcilable with the new urban lifestyle. Movie consumption was first and foremost a local activity. But neither the social influence of the local cinema nor the symbolic frontiers dividing the city could confine movie lovers. The expansion of the cinema generated new flows of moviegoers throughout the city and helped Tunisians to reclaim the public space. In the post-war years, the movie theaters of the “European” center became a place of conviviality for an educated youth whose urban identity would be rooted there.